A rare cause of wheezing infant: Bronchogenic cyst - Vegesna Sunita; YVSS Murty; M Srinivasa Rao; K Sindhura (Wolters Kluwer Medknow Publications, 2015)
A wheezing infant is one of the most common case scenarios that a pediatrician encounters in his office practice. A 3-month-old male child was admitted with persistent wheezing unresponsive to standard management. This prompted us to undertake a detailed diagnostic evaluation including computed tomography chest that revealed the presence of a bronchogenic cyst. The cyst was excised, and the child improved symptomatically. Although uncommon, bronchogenic cysts contribute an important group of lesions, which need to be considered in the differential diagnosis of a wheezing infant. This case report attempts to highlight the importance of considering alternative diagnosis in a wheezing infant when he fails to respond to standard management.